Low-Valent Iron Mono-Diazadiene Compounds: Electronic Structure and Catalytic Application - Lichtenberg, Crispin; Adelhardt, Mario; Gianetti, Thomas L.; Meyer, Karsten; De Bruin, Bas; Gruetzmacher, Hansjoerg (ACS Catalysis, 2015)
A series of monodiazadiene diolefin iron compounds, [Fe(trop2dad)(L)] (4; L = neutral ligand), has been prepared by one-electron oxidation of the FeI species [NaFe(trop2dad)(thf)3] (dad = diazadiene; trop = 5H-dibenzo[a,d]cyclohepten-5-yl). The electronic structures of compounds 4 were investigated by NMR and Mössbauer spectroscopy, single-crystal X-ray diffraction, solid- and liquid-phase magnetic susceptibility measurements, and DFT calculations. Compounds of type 4 with labile ligands L were found to be active (pre)catalysts for the dehydrogenative coupling of (alkyl)amine-boranes. Remarkably high activities were observed, especially for the homogeneous dehydrogenative polymerization of methylamine-borane.
CRIS-Team Scopus Importer:2020-09-14
Keywords: dehydrogenative polymerization; electronic structure determination; homogeneous catalysis; iron diazadiene compounds; methylamine-borane